Preventing Fragility Fractures: A 3-Month Critical Window of Opportunity. (21st June 2021) - Howenstein, Abby; Wally, Meghan; Pierrie, Sarah; Bailey, Gisele; Roomian, Tamar; Seymour, Rachel B.; Karunakar, Madhav
Introduction: Low-energy falls are the leading cause of injury-related morbidity and mortality in the elderly. In the past, physicians focused on treating fractures resulting from falls rather than preventing them. The purpose of this study is to identify patients with a hospital encounter for fall prior to a fracture as an opportunity for pre-injury intervention when patients might be motivated to engage in falls prevention. Materials & Methods: A retrospective analysis of all emergency room and inpatient encounters in 2016 with an ICD10 diagnosis code including "fall" across a tri-state health system was performed. Subsequent encounters with diagnosis of fracture within 2 years were then identified. Data was collected for time to subsequent fracture, fracture type and location, and length of stay of initial encounter. Results: There were 12, 382 encounters for falls among 10, 589 patients. Of those patients, 1, 040 (9.8%) sustained a subsequent fracture. Fractures were most commonly lower extremity fractures (661 fractures; 63.5%), including hip fractures (447 fractures; 45.87%). Median time from fall to fracture was 105 days (IQR 16-359 days). Discussion: Falls are an important, modifiable risk factor for fragility fracture. This study demonstrates that patients are presenting to the hospital with one of the main modifiable risk factors for fracture within a time window that allows for intervention. Conclusions: Presentation to the hospital for a fall is a vital opportunity to intervene and prevent subsequent fracture in a high-risk population.